Legal Analysis of Law Enforcement Against the Misuse of Subsidized Fuel in the Province of Bangka Belitung Island - Andri, Yuda; Saliman, Abdul Rasyid; Sukrisno, Wijayano Hadi (GoAcademica Research & Publishing, 2025)
This research aims to examine the forms of abuse of subsidized Fuel Oil (BBM) and analyze the legal review of law enforcement against such acts in the Province of Bangke Belitung Island. The misuse of subsidized fuel not only causes state losses but also directly impacts the community, particularly low-income groups who are intended to be the primary beneficiaries. The research method employed is a normative juridical approach with a legislative focus and case analysis in the region. The research results indicate that subsidized fuel abuse in the Province of Bangka Belitung Island occurs through practices such as hoarding, diversion of distribution, and document forgery. Legally, law enforcement efforts face various challenges, including weak distribution oversight, limited inter-agency coordination, and legal sanctions that have yet to have a deterrent effect. This research recommends strengthening regulations, enhancing supervision, and imposing stricter sanctions to curb the misuse of subsidized fuel and protect community rights.